Sesso, carta e palco: La fabbrica del teatro nelle riviste LGBT+ «Fuori!», «Lambda» e «Babilonia» (1971-1984) - Tosetto, Cristina (Mimesis Journal, 2019)
Although theatre and cross-dressing have represented the main way to explore sexuality and gender’s identities for Italian homosexuals movements (including the LGBT+ communities) during the 70’s, it is not clear how these movements’ magazines managed to become factories of queer theatre. Their pages, in fact, allowed to revise and imprint true life experiences, which were shared and gave rise to queer practices. Theatre, therefore, became a therapeutic and explorative instrument to fight against sexual and gender’s homogeneity.